Collapse analysis of a wind turbine tower with initial-imperfection subjected to near-field ground motions. (February 2021) - Xu, Yazhou; Ren, Qianqian; Zhang, Hui; Shi, Wenhao
Graphical abstract: Highlights: Seismic performance of a 1.5 MW land-based wind turbine is investigated. The velocity pulse effects of near-field records are studied and compared. The imperfection sensitivity of this wind turbine is evaluated. Collapse analysis is carried out by the incremental dynamic analysis method. Seismic design of wind turbines should consider the pulse-type near-field effect. Abstract: As a slender thin-walled structure, wind turbines may be susceptible to pulse-type near-field seismic records. In order to study the effects of near-field records on the imperfection sensitivity and collapse modes of a 1.5 MW land-based wind turbine, two types of finite element model (FEM) are established and investigated through ABAQUS, i.e. FEM with and without initial welding imperfection. The horizontal displacement, horizontal acceleration, shear force and bending moment are investigated and compared. Finally, the incremental dynamic analysis is carried out to study the imperfection sensitivity and collapse analysis of this tower. The results show that the seismic response of this wind turbine subjected to pulse-type near-field seismic records are all significant larger than those under the excitation without velocity pulses. The presence of imperfections increases the variability of the seismic response of this wind turbine, and different defect amplitudes will affect the location of the plastic hinge on the tower. The plastic hinge is easy to occur at approximately 1/2–3/4 height of the tower under the strong pulse-type near-field earthquake excitation. The welding imperfection can significantly reduce the intensity of ground motion required for the nonlinear response of the wind turbine tower, especially for that under pulse-type near-field seismic excitation.